Determination of volumetric concentration of solids in vertical pipeline hydrotransport - Zych Marcin; Hanus Robert; Petryka Leszek; Strzępowicz Anna; Zych Piotr (EPJ Web of Conferences, 2016)
This paper presents an application of radioisotopes with reference to the determination of the solid phase volumetric concentration in a hydromixture by calibration of the measuring set. It shows how the gamma absorption equipment consisting of radioactive isotopes 241Am and scintillation probe, may be applied to the measurement of solid particles volumetric concentration in a flow. It is based on fact that the intensity of a gamma beam decreases as it passes through matter. In the described experiments as solid phase the ceramic models representing natural polymetallic ocean nodules were used. The especially constructed calibration stand and obtained relation between the related intensity of radiation and mean volumetric concentration of the solid phase are presented.